Studi Alih Fungsi Lahan Hutan Sagu Sebagai Perumahan Residence Di Kabupaten Jayapura - Musfira Musfira; Harina H.Ohee (Jurnal Planoearth, 2019)
Land problems in urban areas are very complex land issues, high rates of population growth, accompanied by the construction of residential areas, industrial estates and shopping areas which have led to increasing demands for land supply. In line with land use and urban land development, it causes frequent conflicts or land problems. The Nontrol Village of East Sentani District is one of the villages that has a Sago Forest Land which is protected by the Sago Forest Protection Act, and due to water infiltration, the community around the project area is very disturbed by the existence of the project and the income from Sagu begins to decrease , fish catches start to decrease, and pollute clean water. The purpose of this study is to identify the factors related to regulation and the issuance of permits for the construction of Residence Residence in Nindung City in the Sago Forest Protected Area. Analyzing the impact of the construction of the Recidence Nendali City housing on the Environment and Social Conditions of the Nontrol Village Community. The analytical method used to answer the research objectives is the descriptive method, where the descriptive method covers repetitive approaches to the object description at the study location. Research is not only limited to the stages of data collection but also includes analysis and processing of data. Whereas in this study began with collective data collection which was carried out through surveys and direct observations on the study sites which previously carried out literature studies as theoretical basic material.